PERNIKAHAN TIDAK SEIMAN: EKSPOSISI KEJADIAN 6:1-4 DAN IMPLIKASI TEOLOGISNYA BAGI OTONOMI INDIVIDU KRISTEN - Susanto, Viki; Pattinaja, Aska Aprilano; Sitanggang, Martauli Dina Rahayu (Sekolah Tinggi Teologi Bethel The Way Jakarta, 2025)
Various religions view non-faith marriage as a controversial decision and contrary to religious teachings. The reality is that many people, including Christians, enter into marriages outside their faith. This marriage is based on the view that it is an individual right. Furthermore, marriage is seen as a demonstration of love and a pursuit of happiness. This qualitative research uses literature and hermeneutic methods to expose the text of Genesis 6:1-4. The purpose of this research is to examine the meaning of the text of Genesis 6:1-4 through exposition. Then examines the theological implications of this exposition for the autonomy of the Christian individual. The exposition's findings demonstrate that unfaithful marriages contradict God's Word and are based primarily on physical appearance, neglecting spiritual qualities. Unfaithful marriages negatively impact not only the individual Christians themselves but also their families and offspring.